PROCESS OF THE WITCH’S DIALOGUES IN SNOW WHITE AND THE HUNTSMAN MOVIE - Siti Arfah; Rahmah Rahmah (State University of Medan, 2013)
ABSTRACT This study is concerned with Transitivity System, focusing on the Process in Snow White and the Huntsman Movie (the main character of the movie: Ravenna). This study was conducted by using descriptive qualitative design. There are six types of process in 145 clauses. The result of data analysis showed that the numbers in types of process were: Material Process (56.55%), Mental Process (13.1%), Relational Process (24.8%), Verbal Process (3.45%), and Existential Process (2.1%). It means that Material process is the dominant type of process used in Ravenna’s utterances (55.56%). The reason why material process was the most dominant was Ravenna displayed action scenes in the movie. Then the material process influences her act became action scene.Keywords: Functional Grammar, Transitivity, Process.